Bacteriophage therapeutics to confront multidrug‐resistant Acinetobacter baumannii ‐ a global health menace. Issue 3 (6th July 2021) - Rai, Sandhya; Kumar, Amod
Summary: We have already entered the post‐antibiotic era as the outbreaks of numerous multidrug‐resistant strains in the community as well as hospital‐acquired infections are ringing alarm bells in the health sector. Acinetobacter baumannii is one such pathogen that has been considered a worldwide threat as it acquires multidrug resistance. It is one of the most challenging hospital‐acquired pathogens as World Health Organization has listed carbapenem‐resistant A . baumannii as a critical priority pathogen with limited therapeutic options. There is an urgent need to develop novel strategies against such pathogens to tackle the global crisis. Bacteriophages (phages), especially the lytic ones have re‐emerged as a potential therapeutic approach. This review encompasses vast majority of phages against A . baumannii strains with special references related to single phage or monophage therapy, use of phage cocktails, combination therapy with antibiotics, use of phage‐derived enzymes like endolysins and depolymerases to combat the pathogen and explore their therapeutic aspects. The concurrent ecological as well as evolutionary interplay between the phages and host bacteria demands in depth‐research and knowledge, so as to utilize the maximum potential of the bacteriophage therapy.